Publisher Correction: Lessons learned and implications of early therapies for coronavirus disease in a territorial service centre in the Calabria region: a retrospective study. - Scaglione, Vincenzo; Rotundo, Salvatore; Marascio, Nadia; De Marco, Carmela; Lionello, Rosaria; Veneziano, Claudia; Berardelli, Lavinia; Quirino, Angela; Olivadese, Vincenzo; Serapide, Francesca; Tassone, Bruno; Morrone, Helen Linda; et al. (BMC Infectious Diseases, 2022)
Publisher Correction: BMC Infectious Diseases (2022) 22:793 https://doi.org/10.1186/s12879-02... In the original publication of this article [[1]] the footnotes of Figure 1 were accidentally omitted during the publication process. 1Patients affected by haematological malignancies/autoimmune diseases or treated with immunosuppressive drugs or transplant receivers; 2First choice in patients with eGFR > 30 ml/min and no major drug interactions; 3Useful in patients with eGFR > 30 ml/min if major drug interactions contraindicate nirmatrelvir/ritonavir or in patients with dysphagia; 4For use in patients with severe renal insufficiency and/or partially immunised (i.e., previous SARS-CoV-2 infection, vaccination course incomplete or completed more than 6 months before); 5mAbs therapy was chosen considering local epidemiology of variants of concern Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.